Education in artistic and humanitarian terms: analysis of three innovators projects - Fernández Antón, Estefanía (Pulso. Revista de educación, 2018)
The Modern School of Ferrer Guardia and the Pedagogical Missions are projects that were created with the aim to bring the best education to the general population. Decades later, several other educational alternatives with the same aim have emerged. Learning Communities are one such example. This study explores education in an artistic and humanitarian sense, an area of interest in these initiatives. For this purpose, we employ qualitative method and research techniques including interviews, observation and documentary analysis. From the data, we found that the proposals are in contact with art through music, theatre, poetry, etc. Also, they promote feelings of solidarity.